Effectiveness of Antiseizure Medication Duotherapies in Patients With Glioma: A Multicenter Observational Cohort Study. (6th September 2022) - van der Meer, Pim B.; Dirven, Linda; Fiocco, Marta; Vos, Maaike J.; Kouwenhoven, Mathilde C.M.; van den Bent, Martin J.; Taphoorn, Martin J.B.; Koekkoek, Johan A.F.
Abstract : Background and Objectives: About 30% of patients with glioma need an add-on antiseizure medication (ASM) due to uncontrolled seizures on ASM monotherapy. This study aimed to determine whether levetiracetam combined with valproic acid (LEV + VPA), a commonly prescribed duotherapy, is more effective than other duotherapy combinations including either LEV or VPA in patients with glioma. Methods: In this multicenter retrospective observational cohort study, treatment failure (i.e., replacement by, addition of, or withdrawal of an ASM) for any reason was the primary outcome. Secondary outcomes included (1) treatment failure due to uncontrolled seizures and (2) treatment failure due to adverse effects. Time to treatment failure was estimated from the moment of ASM duotherapy initiation. Multivariable cause-specific Cox proportional hazard models were estimated to study the association between risk factors and treatment failure. The maximum duration of follow-up was 36 months. Results: A total of 1, 435 patients were treated with first-line monotherapy LEV or VPA, of which 355 patients received ASM duotherapy after they had treatment failure due to uncontrolled seizures on monotherapy. LEV + VPA was prescribed in 66% (236/355) and other ASM duotherapy combinations including LEV or VPA in 34% (119/355) of patients. Patients using other duotherapy vs LEV + VPA had a higher risk of treatment failure for any reason (cause-specific adjusted hazard ratio [aHR] 1.50 [95% CI 1.07–2.12], p = 0.020), due to uncontrolled seizures (cause-specific aHR 1.73 [95% CI 1.10–2.73], p = 0.018), but not due to adverse effects (cause-specific aHR 0.88 [95% CI 0.47–1.67], p = 0.703). Discussion: This observational cohort study suggests that LEV + VPA has better efficacy than other ASM combinations. Similar toxicities were experienced in the 2 groups. Classification of Evidence: This study provides Class III evidence that for patients with glioma with uncontrolled seizures on ASM monotherapy, LEV + VPA has better efficacy than other ASM combinations.